A statistical study of travelling ionospheric disturbances over the African-European and American sectors - Thaganyana, Golekamang Piet (Rhodes University, Faculty of Science, Department of Physics and Electronics)
This research presents a long-term statistical study of travelling ionospheric disturbances (TIDs) of low- and high-latitude origin over the American and African-European sectors between 2010 and 2018. The TIDs of low latitude origin (hereafter known as poleward TIDs) were studied in both quiet and disturbed conditions, whereas the equatorward TIDs were only studied during quiet conditions. The Kp > 4 and Dst_ -50 nT was used as a criterion for geomagnetic disturbed conditions, while the four geomagnetically quiet days were selected each month based on Kp < 3. Observations of TIDs are made using Global Navigational Satellite Systems (GNSS) total electron content derived data. During quiet conditions, seven and two transhemispheric TIDs were identified over the African-European and American sectors, respectively. The observed TIDs originated from the wintertime hemisphere and propagated into the summertime hemisphere. The horizontal velocity, periods, and horizontal wavelengths of TIDs are in range of cH = 120-274 m/s, 48-80 min and _H = 379-1104 km, respectively. These quiet-time equatorward TIDs have been associated with tertiary gravity waves (GWs) from the dissipation of secondary GWs which are in turn generated from the dissipation of mountain waves (MWs) as a result of excited orographic forcing. The poleward TIDs during geomagnetically quiet conditions over the African and American sectors occur mainly during local daytime. Poleward TIDs were observed mostly in the African-European sector than the American sector. Their horizontal propagation velocities and periods range between 129-280 m/s and 39-70 min over African-European and American sectors. Although the mechanisms responsible for launching quiet-time poleward TIDs have not been established in this study, lower atmospheric processes such as convection systems, sudden stratospheric warming and cold weather fronts may have a role in their generation. During geomagnetic storms in the African sector, almost all poleward TIDs (with the exception of two cases) during the main phase were large-scale with horizontal velocities and periods ranging from 250-503 m/s and 30 min to 2 hours. During recovery phase, poleward TIDs fall under the category of medium scale. In the American sector, the majority of poleward TIDs occurred during the storm's main phase, as opposed to the African-European sector, which experienced a significant number of poleward TIDs during the recovery phase. The periods and horizontal velocities of TIDs range from 45 min-1.5 h and 180-296 m/s during main phase. During the recovery phase, the horizontal velocity and period range from 177-271 m/s and 40-1.5 h, respectively. Overall, it has been shown that statistically, changes in equatorial electrodynamics related to enhanced eastward electric _eld and hence increased equatorial electrojet (vertical E_B drift) correlates highly with the reported poleward TIDs.
Keywords: Sudden ionospheric disturbances; Global Positioning System; Gravitational waves; Geomagnetic storm; Ionosphere